2022
DOI: 10.2113/2022/4503366
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mechanical Properties and Failure Processes of Saturated and Unsaturated Slate from Sichuan-Tibet Plateau Area, China

Abstract: Water content significantly affects the physical and mechanical properties of rock and can cause rock mass to become unstable. This, in turn, can cause geologic disasters such as water inrush and surrounding rock deformation. Uniaxial compression experiments on slate samples drilled from the surrounding rock of a tunnel in the Chinese Sichuan-Tibet Plateau area were performed coupled with acoustic emission (AE) monitoring. The changes in mechanical properties and failure processes of unsaturated and saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The porosity value significantly influences rocks' uniaxial compressive strength values due to the reaction between rock mineral grains [9]. The strength of the rock binding force affects the compactness between rock grains; if the binding force is strong, it produces a hard rock with a high uniaxial compressive strength value, and vice versa, if the binding force between the grains is weak, it produces a rock that is less compact and forms many pores filled with water or air, so that the uniaxial compressive strength value is low.…”
Section: Uniaxial Compressive Strength (Ucs) Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The porosity value significantly influences rocks' uniaxial compressive strength values due to the reaction between rock mineral grains [9]. The strength of the rock binding force affects the compactness between rock grains; if the binding force is strong, it produces a hard rock with a high uniaxial compressive strength value, and vice versa, if the binding force between the grains is weak, it produces a rock that is less compact and forms many pores filled with water or air, so that the uniaxial compressive strength value is low.…”
Section: Uniaxial Compressive Strength (Ucs) Analysismentioning
confidence: 99%
“…Several researchers have concluded that water content significantly impacts changes in the structure and characteristics of rocks [9], so the strength of various rocks due to saturation can be reduced by up to 90%. Rock strength increases when saturation is low and decreases significantly when saturation is high [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that the peak strength and elastic modulus of saturated granite are lower than those of dry granite. The softening effect of water content on the strength of slate was further investigated via indoor experiments (Zhang et al [12], Lv [13], Chen et al [14]), and their results showed that the water content can weaken the mechanical properties of slate. Cai et al [15] found that the calcite cementation between particles gradually dissolved and the density and width of intergranular cracks increased after the dry-wet cycle, which may be the reason for the deterioration of the mechanical properties of sandstone.…”
Section: Introductionmentioning
confidence: 99%